How useful are the equity analysts’ report? evidence from Malaysia - Mohd Thas Thaker, Hassanudin; Mohamad, Azhar; Mustaffa Kamil, Nazrol Kamil; Duasa, Jarita (HIKARI Ltd., 2018)
Using 657 Malaysian sell-side analyst recommendations from January 2010 until December 2015, this paper documents the usefulness of equity analyst reports to investors. The research findings revealed that target price and earnings forecast had a significant association with stock return. However, trading volume was shown to have an insignificant relationship with the return. Overall, our results indicate that the information content in the analyst report contained only 66.67% explanatory vis a vis stock return and only target price and earnings forecast were useful. This paper is expected to add value in enriching the literature available on analyst report especially in the context of Malaysian market.